(untitled) (Nóema, 2016)
The essay examines the hierarchical perspective on evolution and traces its history and developments up to the most recent version, developed by Niles Eldredge. This latest version has been the subject of studies and research in the framework of the international project of The Hierarchy Group, a research network consisting of highly qualified scholars coming from the most diverse fields, from evolutionary biology to paleontology, from philosophy of biology to molecular biology. The research has been coordinated by the Department of Biology of the University of Padua and its results have been presented in the volume Evolutionary Theory: A Hierarchical Perspective (Chicago University Press, 2016). The article aims at discussing the scientific contents of the hierarchy theory of evolution and at reflecting as well on the philosophical and theoretical implications involved in such extension of the neo-Darwinian research program to a plurality of levels and evolutionary patterns.